Skill of Teaching Pendidikan Agama Islam untuk Keberhasilan Mengajar di Kelas - Wahyuni, Dinni; Gustika, Fina; Rahman, Taufik (Institut Agama Islam Sumatera Barat, 2024)
This study aims to analyse the application of effective learning methods in improving students' learning achievement in Islamic Religious Education subjects. This research uses a qualitative method with a descriptive approach to explore the supporting factors, obstacles, and strategies for implementing effective learning methods by educators. The results showed that the application of effective learning methods was able to optimise students' learning achievement. This success is supported by several factors, namely the competence of teaching staff, the availability of facilities and infrastructure, and supportive school conditions. However, there are also inhibiting factors such as the low interest and attention of students to learning. Strategies carried out by teachers include adjusting methods to class conditions, understanding the condition of students, and adjusting methods to learning materials. Thus, the application of effective learning methods requires the active role of educators in choosing strategies that suit the needs of students and the learning environment.